A grounded study of the experience of detoxification from psychoactive drugs. - Bartu, Anne (Curtin University, 1998)
The main objective of this thesis was to develop a substantive theory that explained the phenomenon of detoxification from psychoactive drugs such as alcohol, tranquillisers, opioids, and amphetamines in a medical treatment unit for licit and illicit drug users. The other objectives were to (a) determine if the differences reported in earlier studies between licit and illicit drug users in terms of socio-demographic and drug use variables remain extant, and (b) assess the extent of minor psychiatric morbidity among the participants. Both grounded theory and quantitative methods of data collection and analysis were used in the study.The findings of the quantitative component of the study indicated that there were significant differences between licit and illicit drug users in regard to age, drug use characteristics, and completing the treatment program. That is, illicit drug users were younger than licit drug users, more likely to be poly drug users, and drop out of the program. The prevalence of minor psychiatric morbidity among the participants was 93.6%, and was largely independent of socio-demographic and drug use variables. The high prevalence of minor psychiatric morbidity suggests that the majority of participants warranted further follow-up support in the community after they left the treatment unit. The uptake of referrals for follow-up support, however, was 55.9%.The basic or core social psychological problem identified by the constant comparative method of grounded theory was found to have two parts, both of which were interpreted as forms of disequilibrium. The first part of disequilibrium, which was a precursor to treatment, was conceptualised as Hitting the Wall. The events associated with the symbolic "wall" interrupted the participants' drug focussed lifestyles and induced them to enter treatment. These events and problems were not resolved whilst in treatment, they lingered with the participants while they were in the unit, and remained to be addressed when they left. Whilst undergoing detoxification the participants encountered the second part of disequilibrium which was categorised as Incompatibility. The problem of Incompatibility was related to the heterogeneity of the participants and the structure of the treatment program that in many cases was unable to accommodate individual differences and needs.The core or basic social psychological process was conceptualised as Seeking Balance through Hanging In. The participants engaged in this process to deal with the disequilibrium of the precursor problem of Hitting the Wall and the problem of Incompatibility encountered in the unit. Seeking Balance through Hanging In was found to have four phases. The phases were Making the Break, Submitting to Cleansing, Fitting In, and Moving On. The process was linear in that the phases were sequential, and failure to complete a phase meant dropping out of the detoxification program. The experience of detoxification was modified by several contextual conditions. These were the physical enviroment, the participants' expectations of withdrawal symptoms, and the workload of the staff.The substantive theory, Seeking Balance through Hanging In, integrated all emergent categories, and explained the experience of the phenomenon of withdrawal from psychoactive drugs in a particular context. Recommendations for further research include testing the described phases and relationships of the substantive theory in similar environments, exploring the importance of the modifying conditions on client outcomes, and undertaking follow-up studies to determine the outcomes of those who completed the program as compared to the outcomes of those who dropped out. In addition, further studies are recommended to assess the transientness of the level of minor psychiatric morbidity detected among the participants in this study.The findings of this study make an important contribution to understanding the experience of detoxification from the perspective of the participants. The substantive theory has implications for clinical practice, professional education, management, and further research.